Ablation of the epithelial‐specific splicing factor Esrp1 results in ureteric branching defects and reduced nephron number. Issue 10 (28th July 2016) - Bebee, Thomas W.; Sims‐Lucas, Sunder; Park, Juw Won; Bushnell, Daniel; Cieply, Benjamin; Xing, Yi; Bates, Carlton M.; Carstens, Russ P.
Abstract : Background: Abnormalities in ureteric bud (UB) branching morphogenesis lead to congenital anomalies of the kidney and reduced nephron numbers associated with chronic kidney disease (CKD) and hypertension. Previous studies showed that the epithelial fibroblast growth factor receptor 2 (Fgfr2) IIIb splice variant supports ureteric morphogenesis in response to ligands from the metanephric mesenchyme during renal organogenesis. The epithelial‐specific splicing regulator Esrp1 is required for expression of Fgfr2‐IIIb and other epithelial‐specific splice variants. Our objective was to determine whether Esrp1 is required for normal kidney development. Results: Ablation of Esrp1 in mice, alone or together with its paralog Esrp2, was associated with reduced kidney size and increased incidence of renal aplasia. Three‐dimensional imaging showed that embryonic Esrp1 knockout (KO) kidneys had fewer ureteric tips and reduced nephron numbers. Analysis of alternative splicing in Esrp‐null ureteric epithelial cells by RNA‐Seq confirmed a splicing switch in Fgfr2 as well as numerous other transcripts. Conclusions: Our findings reveal that Esrp1‐regulated splicing in ureteric epithelial cells plays an important role in renal development. Defects in Esrp1 KO kidneys likely reflect reduced and/or absent ureteric branching, leading to decreased nephron induction secondary to incorrect Fgfr2 splicing and other splicing alterations. Developmental Dynamics 245:991–1000, 2016 . © 2016 The Authors. Developmental Dynamics published by Wiley Periodicals, Inc. on behalf of American Association of Anatomists. Key findings: Abnormalities in Ureteric bud (UB) branching morphogenesis lead to congenital anomalies of the kidney and reduced nephron numbers associated with chronic kidney disease (CKD) and hypertension. We investigated the consequences of ablating the epithelial‐specific splicing regulator Esrp1 on renal organogenesis and determined that Esrp1 KO mice have reduced kidney size, fewer ureteric tips, reduced nephron numbers, and increased incidence of renal aplasia. Analysis of alternative splicing in Esrp null ureteric epithelial cells by RNA‐Seq identified numerous alterations in splicing. These findings reveal that Esrp1 regulated splicing in ureteric epithelial cells plays an important role in the kidney and illustrate the importance of alternative splicing for normal renal organogenesis.